Deciphering the regulatory network of postharvest quality deterioration in waxy corn through integrated transcriptomic and metabolomic profiling - Mance Zhang; Junxiang Wang; Xiangyi Lan; Tao Guo; Meiying Li; Zilu Wang; Jianglan Peng; Xuemei Zhong; Hongwei Wang; Min Zhu; Jianzhou Qu (Postharvest Biology and Technology, 2026)

The progress of mitochondrial function and transfer in stem cell regulation and therapy - Yubing Zhang; Zhuojian Qu; Zhiliang Guo; Lijuan Zhang; Hong Li; Xiaoyun Zhang; Xiumei Guan; Xiaodong Cui; Wenxu Wang; Min Cheng (Journal of Physiology and Biochemistry, 2026)

Global prioritization of PFAS in groundwater based on multi-scale evaluation of national and source-level data - Yan Zhou; Jinhong Tao; Weiling Tang; Fuyang Huang; Min Fan; Fei Liu; Faqin Dong; Shen Qu (Journal of Environmental Chemical Engineering, 2026)

Hydrogen bond accessibility engineering enables water-rich and mechanically robust chitosan hydrogels - Xiaoye Wang; Min Liu; Furui Qu; Siyi Ma; Xiguang Chen; Jiahao Liu; Chao Feng (Carbohydrate Polymers, 2026)

Light-driven soft actuator with integrated fiber force sensing based on GO/PDMS-AuNBPs composite film - Haowen Xia; Jian Qu; Jinjian Li; Wenxue Li; Min Li; Jingfu Ye; Weijiang Xu; Yi Liu; Shiliang Qu (Chemical Engineering Journal, 2026)

A Novel ARTP-derived Bacillus megaterium Mutant with Enhanced Salt Tolerance and Plant Growth Promotion in Saline–alkali Soil - Min Sun; PengFei Qiu; XinJie Yuan; QiLi Zhu; ZhenXing Peng; JiMin Lv; HongShun Li; JunPing Bao; YanQing Wei; ShuDong Qu; XianShun Ren; ZiHao Wang; et al. (Current Microbiology, 2026)
Soil salinization seriously threatens global food security with continuously expanding affected areas. Bacillus megaterium -based bioinoculant serves as an eco-friendly strategy for saline–alkali land remediation, whereas wild-type (WT) strains generally exhibit poor salt–alkali tolerance. To address this limitation, atmospheric and room temperature plasma (ARTP) mutagenesis combined with a microbial microdroplet culture (MMC) high-throughput screening system was adopted to screen high salt-tolerant B. megaterium mutant followed by multi-omics characterization. Using WT B. megaterium LD (CGMCC No.21828) as the original strain, a mutant library was constructed via optimized ARTP treatment, and the elite mutant SLD48 was isolated under dynamically increasing salt gradients. Compared with the wild type, SLD48 possesses a larger genome of 6,252,538 bp and acquires 28 extra functional genes including spoIVCA and pJ_gene0003 . Intracellular osmoprotectants (proline, glycine betaine) and antioxidant α-tocopherol were markedly accumulated in SLD48. moreover, exogenous supplementation of these substances in the culture medium can effectively alleviate the damage caused by salt stress to the cells. In pot trials with saline–alkali soil, the rhizosphere colonization of SLD48 reached 3.52 × 10⁵ CFU/g (2.46-fold of LD), and maize shoot fresh weight increased by 40.5% after inoculation. Collectively, this work confirms that mutant SLD48 is a promising microbial resource for saline–alkali soil improvement and crop yield promotion.

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

The chelation mechanism, stability and calcium absorption activity of Ruditapes philippinarum peptide‑calcium chelate - Shiyuan Wang; Yaokuan Wang; Fangchen Li; Qiao Jin; Wei Li; Tanye Xu; Min Qu; Changqing Tong (Food Chemistry, 2026)

Stable isotopic niche analysis of the food web in the typical coral reefs of the South China Sea - Chang Sun; Pei Qu; Zhenwei Sun; Jilin Liang; Yuanchao Li; Yulong Zhang; Zongling Wang; Xuelei Zhang; Min Pang (Journal of Oceanology and Limnology, 2026)

Straw return combined with controlled-release urea enhances wheat yield and soil fertility by regulating soil organic carbon fractions: a 10-year field experiment - Yongxiang Gao; Zhaoming Qu; Haojie Feng; Zhiguang Liu; Min Zhang; Yanli Liu; Ronghui Ma; Chengliang Li (Plant and Soil, 2026)

Pulmonary effect of 2D MXenes in mice: Immune cell responses and disrupted hematopoiesis - Gang Tang; Min Li; Jiexia Cheng; Ziniu Wang; Guangxuan Wang; Jianbo Shi; Jonathan W.C. Wong; Jie Gao; Dou Wang; Guohao Zhang; Li Zeng; Yanhua Wang; et al. (NanoImpact, 2026)

IL-33 Regulates the Phenotypic Transformation of Reactive Astrocytes via PENK-ERK/MAPK Pathway in Parkinson’s Disease - Yi Qu; Zhijuan Mao; Danlei Wang; Ke An; Haoheng Yu; Qixiong Qin; Jingyi Li; Yongjie Xiong; Zhe Min; Zheng Xue (Neuroscience Bulletin, 2026)
Interleukin-33 (IL-33) regulates immune responses in central nervous system diseases. This study investigates the effect of IL-33 on astrocyte phenotypic transformation in Parkinson’s disease (PD). The associations of IL-33, soluble growth-stimulating expression gene 2 (sST2), with PD severity and clinical symptoms were examined. IL-33 supplementation and knockdown were applied in vivo and in vitro to assess IL-33’s impact on neuron loss, astrocyte polarization, and inflammation. Transcriptome sequencing was conducted to identify hub genes and pathways regulated by IL-33 in astrocytes, with validated in primary astrocytes. Plasma sST2 levels were elevated in PD patients and correlated with PD severity, while IL-33 decreased with disease progression. In PD models, IL-33 supplementation improved PD-like symptoms and A2 astrocyte polarization. Conversely, IL-33 knockdown worsened PD-like symptoms and neurotoxic polarization. RNA-seq identified the PENK-ERK/MAPK pathway as the key regulator of IL-33-mediated astrocyte transformation. In conclusion, IL-33 plays a crucial role in regulating astrocytes in PD.

Machine learning-based identification of basement membrane-related signature to predict recurrence and immunotherapy benefit in bladder cancer - Min Weng; Xiaojun Wang; Yating Zhan; Yangyang Guo; Zejun Yan; Liangchen Qu; Yadong Liu; Chaoyue Chen (Immunologic Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Wettability UV-switchable TiO2-based surface molecularly imprinted adsorbent for selective phenol removal and its function mechanisms - Boxi Jing; Lei Qin; Yong Zhong; Min Zhang; Yun Qu; Yongzhen Yang; Xuguang Liu (Journal of Environmental Sciences, 2026)

Spatial distribution, contamination characteristics and health hazard potential of soil potentially toxic elements under different reclamation modes in coal mining subsidence areas - Min Tan; Xuanxuan Li; Ruoyun Nian; Xiyuan Song; Jihong Dong; Junfeng Qu; Ming Hao (Environmental Monitoring and Assessment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Metabolomics-based reveals the relation between internal metabolism and storage quality of sesame harvested by machine at different speeds - Ling-Yu Qu; Shu-Guang Gao; Di-Chen Gong; Jing-Wen Zhao; Yun-Xuan Hu; Xiao-Tian Zhu; Han-Zhe Zhang; Hua-Min Liu; Hong-Mei Miao (Food Research International, 2026)

Layered nitrogen application drives changes in nitrogen nutrition status of wheat by affecting key soil microbial clusters - Yang Zhou; Pengjia Wu; Yanjie Qu; Shengyan Pang; Haimeng Mu; Min Yang; Xiang Lin; Dong Wang (European Journal of Agronomy, 2026)

Population pharmacokinetic modeling and Monte Carlo simulation–based dosing optimization of trimethoprim–sulfamethoxazole in critically ill patients - Min Wang; Chen Li; Xiangxiang Fu; Fangling Wang; Xiaojun Zhou; Bingli Zhang; Wenya Xu; Liqiu Liang; Zhenlin Lei; Hengxing Qu; Ling Xie; Lili Zhong; et al. (European Journal of Clinical Pharmacology, 2026)

Dietary bile acids supplementation enhances growth performance, nutrient digestion, hepatic function, rumen fermentation, and modulates quorum sensing in culled ewes - Chang Liu; Lin Li; Min Li; Kehui Ouyang; Mingren Qu; Qinghua Qiu (Animal Feed Science and Technology, 2026)

Environmental aquatic chemistry in the Research Center for Eco-Environmental Sciences: Efforts for cleaner water - Gang Liu; Meng Sun; Weijun Zhang; Deyin Hou; Hong Zhang; Yaohui Bai; Wei An; Chao Liu; Wenzheng Yu; Tao Zhang; Fubo Luan; Jinmiao Zha; et al. (Journal of Environmental Sciences, 2026)

Synthesis strategies, characterization techniques, and prospects of defect-engineered single-atom catalysts for electrocatalysis - Min Yang; Mingyuan Pang; Haohao Zhang; Juan An; Zifan Wang; Jiajia Ye; Zhen Kong; Yuanyuan Du; Jiayu Qu; Chenxi Li; Jibin Song (Fuel, 2026)

Plasmid-mediated modulation of Listeria monocytogenes biofilm formation via TCS/PTS signaling: Implications for food contamination control - Jing Wang; Hui-Min David Wang; Yang Qu; Ting Lin; Changyan Zhou; Zijie Lin; Yangtai Liu; Zhuosi Li; Qingli Dong; Yujuan Suo (Food Research International, 2026)

Analysis of phenomics, metabolomics and transcriptomics reveals the differences in fruit quality between on-tree bagged and non-bagged apples - Yuan Zhao; Yinxin Tang; Ritao Qu; Jing Guo; Yufei Gu; Min Xiao; Chengwei Wu; Qi Pan; Manyu Zhang; Yuandi Zhu (Food Chemistry, 2026)

Integrated lipidomics and transcriptomics reveal the tissue-specific regulatory mechanisms of dietary sodium butyrate on adipose tissue in lambs - Yue Zhang; Xiaotong Li; Hongbo Qu; Min Zhang; Lina Sun; Ye Jin (Food Bioscience, 2026)

Carboxymethyl cellulose-reinforced adhesive bio-patch for sealing wet tissue defects and bioelectronics - Jianpeng Zhang; Haofan Qu; Qiaoling Li; Gongwei Tian; Qingyang Wu; Min Zhang; Jianguo Li; Shengchang Lu; Dianpeng Qi; Hui Wu (Chemical Engineering Journal, 2026)

Investigation of the synthesis and antioxidant activity of novel derivatives of the natural compound daidzein and the quantitative structure–activity relationships - Lai Xinyue; Li Xin; Luo Min; Yang Weiqing; Zhang Aigui; Qu Zhonghua; Li Zicheng; Zixing Ma; Huang Ziyan; Ma Menglin (Natural Product Research, 2026)

Insights into co-occurrence characteristics and interplay of microbial communities and environmental pollutants on biofilm-colonized microplastics in mangrove ecosystems - Tao Yang; Xudong Ye; Xi Deng; Jun Mu; Min Liu; Jianhui Lin; Yuangao Qu; Yingxu Zeng (Water Research, 2026)

Editor's Note to “Factors associated with spatial distribution of severe fever with thrombocytopenia syndrome” [Sci. Total Environ. 750 (2021), 141522] - Ji-Min Sun; Hai-Xia Wu; Liang Lu; Ying Liu; Jiang-Ping Ren; Wen-Wu Yao; Hong-Hua Qu; Qi-Yong Liu (Science of The Total Environment, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Roles and clinical implications of N6-methyladenosine in digestive system tumors - Shixin Luo; Lusheng Liu; Min Sun; Jianwei Wang; Fangyu Sui; Miao Zhang; Xinyu Wu; Miao Qu (Mutation Research - Reviews in Mutation Research, 2026)

Phase-resolved multi-path drivers of PM2.5 evolution in eastern China under Clean Air Actions and carbon neutrality scenarios - Yasong Li; Lili Shen; Dandan Wei; Tijian Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie; Yanjin Wang (Journal of Hazardous Materials, 2026)

Metal sulfide-based electrocatalysts for water splitting: From rational design to advanced applications - Yi Liu; Yijun Wu; Xiantuo Chen; Yongmin Ying; Jili Wen; Huanan Wang; Le Chen; Yingsu Qu; Min Li; Jiang Wu; Zaiguo Fu (Fuel, 2026)

Revealing riverine DOM dynamics along an anthropogenic land-use gradient by integrating biogeochemical and hydrological processes - Jiajun Xu; Ting Wang; Randy A. Dahlgren; Feng Gao; Yingqiang Sun; Hanqin Xu; Yang Jia; Min Wang; Wenli Qin; Bing Liu; Liyin Qu; Zengling Ma (Journal of Hydrology, 2025)

Inhibitory effects of nisin and ε-polylysine on the microbial cell structure and physiological function of Bacillus amyloliquefaciens and applications in bread preservation - Min Qu; Xin Zhang; Xiuqing Zhu; Jingbo Kang; Linlin Liu; Mingshou Lv; Ying Zhu; Bingyu Sun (Food Bioscience, 2025)

Enhanced tetracycline hydrochloride removal by ultra-microporous phosphorus-doped KOH-activated microalgal biochar: Adsorption performance and mechanistic insights - Bing Liu; Weihao Li; Yiwen Huang; Wenli Qin; Min Wang; Yang Jia; Hanqing Xu; Liyin Qu; Hongbin Jiang; Chao Wang; Zengling Ma (Environmental Research, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Partially empirical model-based water depth retrieval in shallow sea using GF5-AHSI hyperspectral remote sensing data: a case study on Meizhou Bay in Fujian Province, China - Xiaoai Dai; Yunfeng Shan; Cheng Li; Hao Chen; Tangrui Dai; Ge Qu; Tianyi Xie; Chengbo Tong; Htun Naing; Min Zhang (Frontiers of Earth Science, 2025)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Effects of ultrasound on the structure and properties of soy protein gels prepared with different 11S/7S ratios - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Hydrocolloids, 2025)

Impacts of different types of wastewater discharge on plankton community structure in the receiving rivers of the Yangtze River - Rui Bian; Shier Huang; Xiaofeng Cao; Weixiao Qi; Jianfeng Peng; Huijuan Liu; Min Chen; Yufeng Chen; Jiuhui Qu (Environmental Pollution, 2025)

Synergistic air pollution and CO2 emission reduction in China's iron and steel industry based on real-time monitoring data - Ling Tang; Qing Yu; Jiabao Qu; Ruxing Wan; Min Jia; Shuangyue Qian; Song Lv; Jieyi Li; Shuo Qi (Environmental Pollution, 2025)

A novel strain-based deformation monitoring method for subsea free-spanning pipelines - Tao Jiang; Zi-min Xie; Jia-jian Wang; Dong-sheng Li; Chun-xu Qu (Engineering Structures, 2025)

Biohybrid technologies for CO2 conversion to fuels and chemicals: Advances in bio-electro-, bio-photoelectro-, and bio-photocatalysis - Lu Chen; Yuan Wen; Min Chen; Xiaoqiang An; Jiuhui Qu (Bioresource Technology, 2025)

Effects and mechanisms of MSCs and MSC-derived exosomes in regulating ferroptosis - Zhiliang Guo; Zhuojian Qu; Yubing Zhang; Donghua Xu; Lijuan Chu; Min Cheng (Journal of Physiology and Biochemistry, 2025)

miR-133b regulation of wbp2 in ovaries is conserved among teleosts - Jiayu Zhou; Qianwen Min; Xubing Ba; Zhaoqiu Qu; Zhenjun Zhuang; Biao Yuan; Xin Yi; Ruojing Li; Na Zhao; Bo Zhang (Acta Oceanologica Sinica, 2025)

Corrigendum to “WWOX attenuates the progression of gallbladder cancer by suppressing cellular glycolysis through the modulation of the P73/HIF-1a signaling pathway” [Tissue Cell 95 (2025) 102885] - Bo Tang; Qi-Cai Qu; Dong-Yun Cun; Xia-Wei Yang; Kun Su; Ren-Chao Zou; Tao Wang; Lian-Min Wang; Tao Wu; Dong Wei; Qiu-Hong Wang (Tissue and Cell, 2025)

Hematopoietic responses to metal-organic frameworks in adult mice following pulmonary exposure - Min Li; Linlin Yao; Yuanyuan Wang; Jie Gao; Junjie Ma; Yaquan Liu; Yun Ding; Xuehan Zheng; Liqun Chen; Runzeng Liu; Li Zeng; Guangbo Qu; et al. (Journal of Environmental Sciences, 2025)

Whole-Brain Monosynaptic Inputs to Parasubthalamic Calretinin Neurons in Mice - Han Guo; Mutian Zhang; Jie Huang; Haifeng Zhou; Min Zhang; Hongdan Wang; Xudong Xu; Xiaoyan Liu; Weimin Qu; Zhili Huang (Molecular Neurobiology, 2025)

Mechanism of dietary Bacillus subtilis in enhancing lamb quality: synergistic regulation of gastrointestinal microflora and host metabolism - Yue Zhang; Hongbo Qu; Yuhan Zhang; Qianyu Liu; Min Zhang; Yueying Guo; Lina Sun; Ye Jin (Food Bioscience, 2025)

WWOX attenuates the progression of gallbladder cancer by suppressing cellular glycolysis through the modulation of the P73/HIF-1α signaling pathway - Bo Tang; Qi-cai Qu; Dong-yun Cun; Xia-wei Yang; Kun Su; Ren-chao Zou; Tao Wang; Lian-min Wang; Tao Wu; Dong Wei; Qiu-hong Wang (Tissue and Cell, 2025)

Dual-solvent-induced persistent nanoscale wet film for controllable two-dimensional molecular crystallization toward polarization-sensitive photodetectors - Yumeng Wang; Lujing Shao; Yu Chen; Shengnan Chen; Yongrui Yang; Fanyi Min; Mengmeng Guo; Wenkun Lv; Zheng Li; Zhiyuan Qu; Lutong Guo; Jie Gao; et al. (Science Bulletin, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Gel-based evaporators for solar desalination of high concentration brines - Zihui Wang; Xinjuan Liu; Yuquan Li; Bowen Wang; Zhongkai Qu; Min Xu; Likun Pan (Desalination, 2025)

Ultraviolet and visible dual-narrowband photomultiplication type organic photodetectors - Xingchao Zhao; Kaixuan Yang; Xiaoling Ma; Min Hun Jee; Hongfei Qu; Shuai Zhang; Yao Ma; Liang Shen; Guangcai Yuan; Qi Yao; Han Young Woo; Fujun Zhang (Chemical Engineering Journal, 2025)

Persistent O3 pollution over the North China Plain during the advancement of East Asian summer monsoon: Process analysis and interannual difference - Libo Gao; Tijian Wang; Xuejuan Ren; Yawei Qu; Hao Wu; Mengmeng Li; Min Xie (Atmospheric Research, 2025)

Taurine related pathways effect the potential domestication of wild Larimichthys crocea adapt to stress environment - Xubing Ba; Zhenjun Zhuang; Zebin Zhou; Jiayu Zhou; Qianwen Min; Biao Yuan; Xin Yi; Ruojing Li; Zhaoqiu Qu; Na Zhao; Bo Zhang (Aquaculture, 2025)

Transcriptome-hormone network analysis tentatively reveals a chalcone synthase 1-dependent pathway for tobacco mosaic virus resistance in tobacco - Fuxin Li; Min Ren; Lihua Li; Jiang Wu; Fengjie Wei; Xiaoling Qu; Ying Tong; Xiuming Wu; Yangyang Sun; Aiguo Yang; Shuai Chen; Yinchao Zhang (Physiological and Molecular Plant Pathology, 2025)

Toxicity Challenges and Current Advancement in Metal–Organic Frameworks (MOFs) for Biomedical Applications - Mubbashar Abbas; Zhiwei Liang; Min Chen; Wei Qu; Suliman Khan; Muhammad Sameer Ashaq; Dongmei Chen; Shuyu Xie (Biological Trace Element Research, 2025)

Transcription factor FOXD3 participates in the immune response of Pinctada fucata martensii by regulating nAChR-5 - Min Yang; Yongge Huang; Xinyi Lin; Zhihan Li; Shilin Zheng; Youmei Qu; Yue Wen Deng; Ronglian Huang; Yu Jiao (Aquaculture, 2025)

Metagenomic analysis reveals differences in antibiotic resistance and transmission risks across various poultry farming models - Yanru Huang; Shuaizhou Zong; Dingting Xu; Jiwei He; Yaru Zhang; Min Qian; Yuxing Li; Bohai Guo; Jianzhong Han; Daofeng Qu (Science of The Total Environment, 2025)

Heat-triggered CRISPR/Cas12a microspheres for one-pot assays - Siying Xie; Shan Shao; Jin Wang; Jing Qu; Ying Cai; Xingyan Lai; Nan Min; Lidan Zhang; Yan Shi; Tingdong Li; Xiaomin Zhang; Bo Peng; et al. (Science Bulletin, 2025)

Differences in the distribution of exogenous nucleotide intake in the colon of neonatal rats and its impact on early-life metabolism, gut, gut microbiota, and skeletal development - Zhihao Qu; LiLi Zhu; Min Guo; Kexin Shang; Peijun Tian; Linlin Wang; Gang Wang; Heng Zhang; Wei Chen (Food Bioscience, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Progestogen is a potential trigger initiating sex inversion in rice field eel (Monopterus albus) - Xiancheng Qu; Jiaoyun Jiang; Min Li; Jianhua Ye; Lisa Pan; Qinhua Zhang; Guofang Zhong; Xinchao Zhu; Yifang Du; Xianhui Li (Fish Physiology and Biochemistry, 2025)

Impact of aerosol-radiation interaction and heterogeneous chemistry on the winter decreasing PM2.5 and increasing O3 in Eastern China 2014–2020 - Yasong Li; Tijian Wang; Qin'geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie (Journal of Environmental Sciences, 2025)

Spatial distribution of potential nitrogen reduction rates and associated microbial communities revealed by metagenomic analysis in Yangtze River sediments - Jiaxun Guo; Aomei Guan; Min Chen; Yufeng Chen; Weixiao Qi; Xiaofeng Cao; Jianfeng Peng; Huijuan Liu; Jiuhui Qu; Zhuoyue Jia; Hongxiu Hu (Environmental Research, 2025)

Short-Chain Fatty Acid Aggregates Alpha-Synuclein Accumulation and Neuroinflammation via GPR43-NLRP3 Signaling Pathway in a Model Parkinson’s Disease - Yi Qu; Ke An; Danlei Wang; Haoheng Yu; Jingyi Li; Zhe Min; Yongjie Xiong; Zheng Xue; Zhijuan Mao (Molecular Neurobiology, 2025)

Trophic transfer of mercury in marine food chains from the offshore waters of Changshan Archipelago - Mingyu Huo; Min Pang; Xuli Ma; Penggong Wang; Chang Sun; Yulong Zhang; Yuchen Gong; Zhenwei Sun; Zhaohui Zhang; Zongling Wang; Pei Qu; Xianxiang Luo (Frontiers in Marine Science, 2025)
Introduction Mercury (Hg) and its organic forms can accumulate in marine organisms, undergoing biomagnification as they transfer through food chains. However, the factors affecting such Hg biomagnification are not fully understood. Methods This study analyzed the biomagnification of total mercury (THg) and methylmercury (MeHg) in marine food chains represented by invertebrates and fish from the offshore waters of Changshan Archipelago, grouped into continuous trophic level (TL) ranges based on nitrogen stable isotopic analysis. Results Concentrations of THg and MeHg ranged from 4.8 ng/g to 115.4 ng/g and 1.8 ng/g to 47.3 ng/g in invertebrates, and from 3.7 ng/g to 102.1 ng/g and 0.5 ng/g to 67.6 ng/g in fish, with TL ranges for invertebrates and fish of 1.27–2.70 and 1.97–3.60, respectively. Hg concentration increased with increasing TLs in both fish and invertebrates. Combined with nitrogen stable isotopic analysis, trophic magnification factors (TMF) were 1.51 and 1.16 for THg and MeHg in fish, and 1.95 and 1.71 for THg and MeHg in invertebrates, respectively, indicating the biomagnification of THg and MeHg in the study area. Further analysis of Hg biomagnification showed higher TMF values of Hg in both invertebrate and fish groups with higher δ 13 C values, suggesting that food sources influenced Hg biomagnification in marine organisms. Discussion Food sources with lower δ 13 C values might reduce biomagnification efficiency of both THg and MeHg within marine fauna. These results aided understanding of Hg biomagnification in marine food chains and provided a reference for developing ways to harness Hg pollution.

Influence of processing points on the flavor of meat balls braised with brown sauce - Xia Qu; Haonan Shi; Chao Chen; Jie Sun; Zixin Deng; Min Li; Zhenyu Wang; Dequan Zhang; Chunjiang Zhang (Food Research International, 2025)

Understanding the effect and mechanism of ε-polylysine on the improvement of tofu storage quality via biofilm inhibition by Bacillus licheniformis and Bacillus amyloliquefaciens - Jingbo Kang; Xin Zhang; Yuyang Huang; Ying Zhu; Linlin Liu; Bingyu Sun; Min Qu; Xiuqing Zhu (Food Bioscience, 2025)

High-performance and short-process sulphur autotrophic denitrification from low-C/N wastewater using novel suspended bio-S0 filters - Rashmi Koju; Yu Cheng; Shujia Gao; Tista Prasai Joshi; Chengzhi Hu; Min Yang; Jiuhui Qu (Journal of Cleaner Production, 2025)

Effect of freezing-thawing treatment on the quality and structure of soymilk gels induced by different coagulants - Ying Zhu; Wenhua Lei; Lidan Qiu; Simiao Liu; Ruqi Guo; Yuyang Huang; Linlin Liu; Mingshou Lv; Bingyu Sun; Min Qu; Ying Sun; Xiuqing Zhu (Food Hydrocolloids, 2025)

Comprehensive analysis of ionomic profiling in Chlorella exposed to chlorpyrifos - Qing-Qing Yu; Yulong Zhang; Shiyuan Zhao; Min Pang; Pei Jiang; Pei Qu (Frontiers in Marine Science, 2025)
Introduction Chlorpyrifos (CPF), a widely used organophosphorus insecticide, is highly toxic to non-target aquatic organisms and has relatively high persistence in water, posing a serious threat to marine ecosystems. However, little is known about the toxicological mechanism of CPF on marine microalgae, which is the main primary producer in the marine ecosystem. Methods This study explored the ion changes of microalgae Chlorella vulgaris under the stress of CPF through Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Results Significant disparities in ionomics among control and treatment group were observed through pattern recognition analysis (principal component analysis, PCA; orthogonal partial least squares discriminant analysis, OPLS-DA), indicating that CPF may impede their growth by disrupting the homeostasis of crucial elements within algal cells. Discussion This study elucidated the inhibitory impact of CPF on green algae growth and its potential mechanism of toxicity through ICP-MS, providing crucial insights for a comprehensive understanding of the influence of organophosphorus pesticides on aquatic ecosystems.

Integrated omics analysis reveals the effect of feeding scarcity on the lipid metabolism and apoptosis in Nibea coibor - Zhaoqiu Qu; Biao Yuan; Ruojing Li; Xubing Ba; Zhenjun Zhuang; Xin Yi; Jiayu Zhou; Qianwen Min; Zhongdian Dong; Na Zhao; Bo Zhang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In situ sulfur-loaded on carbon materials for efficient antibiotic removal under visible light - Shouxin Zhu; Zhexiao Zhu; Jingyi Qu; Can Sun; Zijie Fang; Mingli Qin; Yangben Chen; Xiaolu Xu; Jiahui Lin; Min Liu; Hui Zheng (Journal of Water Process Engineering, 2025)

Effect of freeze-thaw cycles on the quality of Yuba with different protein-lipid ratios on its protein-lipid network system - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Chemistry, 2025)

Accelerating direct formation of α-FAPbl3 by dual-additives synergism for inverted perovskite solar cells with efficiency exceeding 26 % - Min Wang; Liang Li; Jinhui Wang; Hao Huang; Peng Cui; Zhineng Lan; Shujie Qu; Yi Suo; Meicheng Li (Chemical Engineering Journal, 2025)

The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2025)

Why does distilled liquor (Baijiu) have a yellowish color: A comprehensive analysis - Jilei Wang; Qu Li; Yun Sun; Jingwen Liu; Zhao Jiang; Zhuoping Zheng; Li Liu; Xinhui Min; Yougui Yu; Qing Zheng (Food Chemistry, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Elevated pCO2 may increase the edible safety risk of clams exposed to toxic Alexandrium spp. - Min Pang; Yuchen Gong; Hongju Chen; Ying Shi; Zhao Li; Xiuping He; Junhui Chen; Xuexi Tang; Zongling Wang; Xuelei Zhang; Pei Qu (Science of The Total Environment, 2024)

Protective role of Mortierella alpina-derived lipids in resisting root rot in Panax ginseng - Zhijie Qiu; Zhaobei Wang; Shuoye Wang; Jingyi Fei; Zhimiao Qu; Hao Wu; Min Zhao; Hongyan Yang (Rhizosphere, 2024)

Transport network changes and varying socioeconomic effects across China's Yangtze River Delta - Junxi Qu; Tianren Yang; Kyung-Min Nam; Euijune Kim; Yimin Chen; Xingjian Liu (Journal of Transport Geography, 2024)

Heterologous expression of the TaCBF2 gene improves cold resistance in Begonia semperflorens - Huiting Xia; Min Chen; Puyu Ren; Tianxiao Sun; Dandan Zhao; Xiaojie Qin; Fei Li; Weichao Liu; Ying Qu; Yonghua Li; Kaiming Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

An efficient flavonoid glycosyltransferase NjUGT73B1 from Nardostachys jatamansi of alpine Himalayas discovered by structure-based protein clustering - Mingkang Feng; Yuan Liu; Bin He; Hairong Zhong; Axiang Qu-Bie; Min Li; Mengting Luo; Xiaoming Bao; Ying Li; Xinjia Yan; Huachun Sheng; Zhifeng Zhang; et al. (Phytochemistry, 2024)

Induced resistance to control postharvest stem-end rot by methyl jasmonate in mango fruit - Min Li; Xiangxiang Qu; Deqiang Gong; Tianyu Huang; Yu Wang; Yi Yang; Zhaoyin Gao; Zhengke Zhang; Jinhua Sun; Meijiao Hu (Physiological and Molecular Plant Pathology, 2024)

Copper-based photocatalysts with natural organic ligands for efficient removal of tetracycline under visible light - Shouxin Zhu; Can Sun; Zhexiao Zhu; Jingyi Qu; Zijie Fang; Yangben Chen; Jiahui Lin; Xiaolu Xu; Miaoyan Cheng; Min Jiang; Hui Zheng (Journal of Environmental Management, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Deciphering the seasonal dynamics of multifaceted aerosol-ozone interplay: Implications for air quality management in Eastern China - Yasong Li; Tijian Wang; Qin'geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Jiachen Fan; Min Shao; Min Xie (Science of The Total Environment, 2024)

Manipulating Förster interactions between the π-D and π-A Exciplex-Forming hosts and dopants by substituent steric optimization for highly efficient Orange-Red OLEDs - Zi-Qi Feng; Sheng-Yi Yang; Min Song; Zhi-Hao Qu; Zi-Yu Song; Zuo-Quan Jiang; Dong-Ying Zhou; Liang-Sheng Liao (Chemical Engineering Journal, 2024)

Spatial control of nanoreactions on cellulose nanofibers using drop evaporation - Rui Ding; Min Zhang; Lujia Xuan; Zhengyuan Ma; Yixiao Qu; Zheng Liu; Hui He; Ruoyang Chen (Chemical Engineering Journal, 2024)

Spatiotemporal distribution and transport flux of organophosphate esters in the sediment of the Yangtze River - Qinya Fan; Shier Huang; Jiaxun Guo; Yu Xie; Min Chen; Yufeng Chen; Weixiao Qi; Huijuan Liu; Zhuoyue Jia; Hongxiu Hu; Jiuhui Qu (Journal of Hazardous Materials, 2024)

The joint impact of PM2.5, O3, and CO2 on the East Asian Summer Monsoon in 2013 and 2018 due to contrasting emission reduction - Danyang Ma; Tijian Wang; Hao Wu; Yawei Qu; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Natalya Andreeva Kilifarska-Nedialkova (Atmospheric Environment, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Correction to: The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2024)

Inactivation of Aeromonas hydrophila in water by dielectric barrier discharge plasma: Efficiency, mechanism, and application safety - Le Wang; Zhenfei Zhu; Pengcheng Yan; Rong Zhang; Min Zhang; Xiangyu Wang; Guangzhou Qu; Tiecheng Wang; Ronghua Li (Journal of Water Process Engineering, 2024)

Effect-directed analysis of androgenic compounds from sewage sludges in China - Tongtong Xiang; Chunzhen Shi; Yunhe Guo; Jie Zhang; Weicui Min; Jiazheng Sun; Jifu Liu; Xiliang Yan; Yanna Liu; Linlin Yao; Yuxiang Mao; Xiaoxi Yang; et al. (Water Research, 2024)

Contrasting effects of different straw return modes on net ecosystem carbon budget and carbon footprint in saline-alkali arid farmland - Min Hu; Zhongyi Qu; Yue Li; Yunwu Xiong; Guanhua Huang (Soil and Tillage Research, 2024)

Research on explosion hazard and prevention of ultrafine aluminium powder based on orthogonal matrix analysis - Jiao Qu; Ting Zhou; Zhen-Min Luo; Jun Deng; Yang Xiao (Process Safety and Environmental Protection, 2024)

MXene/Ag3PO4 modified PVDF composite membranes for efficient interfacial evaporation and photodegradation - Xiaotong Mu; Lihua Chen; Nannan Qu; Min Yin; Shang Wu; Qimeige Hasi; Chaohu Xiao (Journal of Environmental Chemical Engineering, 2024)

Engineering ZIF-67 loaded nanofibrous membrane with thermal stabilization treatment for efficient photocatalytic CO2 reduction - Pengfei Lin; Xiwei Qu; Bhaskar Jyoti Deka; Chao Hu; Lei Zhao; Dongyun Wu; Chunhai Yi; Min Wei Boey; Muhammad Usman Farid; Alicia Kyoungjin An; Jiaxin Guo (Chemical Engineering Journal, 2024)

Exploring the role of aerosol-ozone interactions on O3 surge and PM2.5 decline during the clean air action period in Eastern China 2014–2020 - Yasong Li; Tijian Wang; Qin'’geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie (Atmospheric Research, 2024)

Insight Into the Effects of Environmental and Structural Factors on the Re-Oxidation of Cr(III) Hydroxides - Min Qu; Huixia Chen; Hongling Zhang; Shuai Jiao; Hongbin Xu (International Journal of Environmental Research, 2024)

Microbial mechanisms in nitrogen fertilization: Modulating the re-mobilization of clay mineral-bound cadmium in agricultural soils - Jun-Feng Wang; Can Liu; Zhi-Min Xu; Fo-Peng Wang; Yun-Yun Sun; Jia-Wei Huang; Qu-Sheng Li (Science of The Total Environment, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Effects of straw returning combined with blended controlled-release urea fertilizer on crop yields, greenhouse gas emissions, and net ecosystem economic benefits: A nine-year field trial - Yongxiang Gao; Yuqing Shao; Jiaqi Wang; Bin Hu; Haojie Feng; Zhaoming Qu; Zhiguang Liu; Min Zhang; Chengliang Li; Yanli Liu (Journal of Environmental Management, 2024)

Effects of glutenin/gliadin ratio and calcium ion on the structure and gelatinity of wheat gluten protein under heat induction - Min Qu; Peixiu Jiang; Ying Zhu; Xiuqing Zhu; Linlin Liu; Yuyang Huang (Food Bioscience, 2024)

Functional analyses of TRAF6 gene in Argopecten scallops - Xiaotong Zhang; Xia Wang; Jieyu Chen; Min Chen; Xia Lu; Junhao Ning; Haijun Liu; Guilong Liu; Xin Xu; Xiaoxu Qu; Kai Yu; He Xu; et al. (Fish & Shellfish Immunology, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

The Middle Miocene lobe-shaped and band-shaped submarine fans in the Lingshui Sag, Qiongdongnan Basin: source-to-sink system, genesis and implication - Xingzong Yao; Congjun Feng; Hongjun Qu; Min Zhang; Daming Li (Acta Oceanologica Sinica, 2024)

A review of quorum sensing regulating heavy metal resistance in anammox process: Relations, mechanisms and prospects - Caiyan Qu; Fan Feng; Jia Tang; Xi Tang; Di Wu; Ruiyang Xiao; Xiaobo Min; Chong-Jian Tang (Critical Reviews in Environmental Science and Technology, 2024)

The inventory of pollutants in brownfield sites: An innovative strategy for prevention and control of soil pollution in China - Ye Li; Tianhao He; Fangfang Ding; Xiaofei Li; Ye Huang; Erkai He; Hongming Cai; Peili Shi; Jian Liu; Yan Li; Ruijuan Qu; Wang Zheng; et al. (Science Bulletin, 2024)

Elucidating drivers of severe wintertime fine particulate matter pollution episodes in the Yangtze River Delta region of eastern China - Lei Shu; Tijian Wang; Jane Liu; Zhixiong Chen; Hao Wu; Yawei Qu; Mengmeng Li; Min Xie (Science of The Total Environment, 2024)

Urbanization reduces fish taxonomic and functional diversity while increases phylogenetic diversity in subtropical rivers - Bo Yang; Xiao Qu; Han Liu; Min Yang; Wei Xin; Weiming Wang; Yushun Chen (Science of The Total Environment, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

Numerical simulation of hydrodynamic performance of pump-jet propulsor with serrated trailing-edge duct under different working conditions - Yu Sun; Li-xin Qu; Huang-hua Peng; Jia-min Guo; Zhi-xin Xiong (Ocean Engineering, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Insight into personal exposure characteristics and health effects of PM2.5 and PM0.25-bound PAHs and their derivatives with different heating ways in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Bin Zhang; Min Gao; Jian Sun; Zhenxing Shen; Linli Qu; Steven Sai Hang Ho; Junji Cao (Environmental Pollution, 2023)

Spontaneous compartmentalization in chitosan - phytate - lignosulfonate microparticles by gas-shearing microfluidics - Qingli Qu; Long Chen; Weixia Cheng; Jules Muhire; Anquan Yang; Jing Wang; Min Xie; Xiaoli Zhang; Dan Huang; Ranhua Xiong; Dong Pei; Chaobo Huang (Chemical Engineering Journal, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Anti-complement factor H (CFH) autoantibodies could delay pristane-induced lupus nephritis - Lin-Lin Li; Zhong-qiu Luan; Ying Tan; Hui Wang; Xiao-Juan Yu; Zhen Qu; Feng Yu; Min Chen (Immunologic Research, 2023)
Purpose Anti-complement factor H (CFH) autoantibodies could be detected in lupus and its significance remained to be elucidated. Herein, we aimed to explore the roles of anti-CFH autoantibodies based on pristane-induced lupus mice. Methods Twenty-four female Balb/c mice were randomly divided into four groups, with one group injected with pristane (pristane group), one group with pristane and then human CFH (hCFH) (pristane-CFH group) 3 times, and the other two as vertical controls, PBS group and PBS-CFH group. Histopathological analysis was performed six months after pristane administration. Levels of hCFH, anti-CFH autoantibodies and anti-dsDNA antibody were detected. Murine IgG (mIgG) were purified and cross-reactivity, epitopes, subclasses and functional analysis were further evaluated in vitro. Results Immunization with hCFH and subsequent development of anti-CFH autoantibodies significantly attenuated nephritis of pristane-induced lupus, including lower levels of urinary protein and serum creatinine, decreased levels of serum anti-dsDNA antibody, greatly ameliorated renal histopathologic damage, decreased IgG, complements (C1q, C3) deposits and lower inflammatory factor (IL-6) expression in glomerulus. Furthermore, the purified mIgG (contained anti-CFH autoantibodies) could recognize both hCFH and murine CFH, and the epitopes were predominantly located in hCFH short consensus repeats (SCRs) 1–4, 7 and 11–14. The IgG subclasses were predominant IgG1. The autoantibodies could enhance the binding between hCFH and C3b, and increase factor I mediated-C3b lysis in vitro. Conclusion Our results suggested that anti-CFH autoantibodies could attenuate pristane-induced lupus nephritis by increasing bio-functions of CFH on regulating complement activation and controlling inflammation.

Comparing the variation and influencing factors of CO2 emission from subsidence waterbodies under different restoration modes in coal mining area - Min Tan; Zhengfu Bian; Jihong Dong; Ming Hao; Junfeng Qu (Environmental Research, 2023)

Highly photoluminescent tryptophan-coated copper nanoclusters based turn-off fluorescent probe for determination of tetracyclines - Tianru Zou; Shaoqing Li; Guixiang Yao; Rui Qu; Wenrong Yang; Hongbin Wang; Wei Tan; Min Yang (Chemosphere, 2023)

Reverberation time control by acoustic metamaterials in a small room - Sichao Qu; Min Yang; Yunfei Xu; Songwen Xiao; Nicholas X. Fang (Building and Environment, 2023)

Study on the assimilation of the sulphate reaction rates based on WRF-Chem/DART - Congwu Huang; Chaoqun Ma; Tijian Wang; Yawei Qu; Mengmeng Li; Shu Li; Bingliang Zhuang; Min Xie (Science China Earth Sciences, 2023)

Inoculation of Escherichia coli enriched the key functional bacteria that intensified cadmium accumulation by halophyte Suaeda salsa in saline soils - Tao He; Zhi-Min Xu; Jun-Feng Wang; Ke Zhang; Fo-Peng Wang; Wan-Li Li; Ping Tian; Qu-Sheng Li (Journal of Hazardous Materials, 2023)

Self-checking dual-modal aptasensor based on hybrid Z-scheme heterostructure of Zn-defective CdS/ZnS for oxytetracycline detection - Pei Song; Ping Qu; Min Wang; Ai-Jun Wang; Yadong Xue; Li-Ping Mei; Jiu-Ju Feng (Analytica Chimica Acta, 2023)

Parerythrobacter lacustris sp. nov., a novel member of the family Erythrobacteraceae isolated from an inland alpine lake - Maripat Xamxidin; Han Dong; Jia-Yan Wang; Wu Qu; Lin Xu; Min Wu (Archives of Microbiology, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Coupling doping and localized surface plasmon resonance toward acidic pH-preferential catalase-like nanozyme for oxygen-dominated synergistic cancer therapy - Yuqing Rao; Guopeng Xu; Zhihua Zhang; Weijie Wang; Chengmei Zhang; Mingwen Zhao; Yuanyuan Qu; Weifeng Li; Min Ji; Yanguo Liu; Yong-Qiang Li (Chemical Engineering Journal, 2023)

The underlying mechanisms of PM2.5 and O3 synergistic pollution in East China: Photochemical and heterogeneous interactions - Yawei Qu; Tijian Wang; Cheng Yuan; Hao Wu; Libo Gao; Congwu Huang; Yasong Li; Mengmeng Li; Min Xie (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

LncRNA PVT1 influences breast cancer cells glycolysis through sponging miR-145-5p - Huan Qu; Xingxing Li; Fei Chen; Min Zhang; Xun Lu; Yun Gu; Mingming Lv; Cheng Lu (Genes & Genomics, 2023)
Background Long-non-coding RNA PVT1 (lncRNA PVT1) can be used as an oncogenic regulatory non-coding RNA (ncRNA) for many cancers. However, its function and mechanism in breast cancer (BRCA) are still not clearly elucidated. Objective We attempt to explain the mechanism of PVT1’s role in breast cancer from different perspectives. Methods We analyzed the expression of PVT1 and its correlation with the breast cancer related clinical data in the The Cancer Genome Atlas (TCGA) database. We used PVT1 overexpression and knockdown lentivirus to infect breast cancer MDA-MB-231 cell line for cell function verification, in vitro using CCK-8 to measure proliferation, flow cytometry to measure apoptosis, transwell test to measure invasion and migration ability, detecting cell extracellular acidification rate (ECAR) to assess glycolysis metabolism and explore the biological functions of PVT1 in breast cancer cells. Transcriptome sequencing was used to analyze the changes of related genes in cells after overexpression of PVT1. In vivo we used a xenograft model to study the effect of PVT1 on breast cancer. Results PVT1 was up-regulated in breast cancer tissues and was positively correlated with the clinical stage of breast cancer patients. Overexpression of PVT1 in vitro promoted cell proliferation, migration and invasion, and promoted tumor growth in vivo. Knockdown of PVT1 led to the opposite biological consequence. Further bioinformatics analysis showed that PVT1 changes the glycolysis metabolism of tumors through regulation of glycolysis-related genes. In addition, the expression of miR-145-5p is negatively correlated with PVT1. We consider the possibility of PVT1 promoting cell proliferation and metastasis by regulating the aerobic glucose metabolism in breast cancer cells through sponging the miR-145-5p. Conclusion Our results reveal a potential pathway for competing endogenous RNA to regulate breast cancer glucose metabolism. PVT1 regulates glycolysis related genes expression by competitively binding to endogenous miR-145-5p in breast cancer cells to change the metabolic phenotype. This may Provide new ideas for precise molecular therapy targets for breast cancer.

High-resolution mapping and evolution of steel stocks and waste in civil buildings: a case study of Changsha, China - Youliang Chen; Qu Gong; Yan Shi; Min Deng (Environmental Science and Pollution Research, 2023)

Simulation and risk assessment of arsenic by Hydrus-3D and CalTOX in a typical brownfield site - Tianhao He; Ye Li; Ye Huang; Erkai He; Yan Li; Liangyu Qu; Fangfang Ding; Ruihe Jin; Mingzhe Han; Lina Yuan; Weizhen Xue; Ruijuan Qu; et al. (Journal of Hazardous Materials, 2023)

Potential roles of IFI44 genes in high resistance to Vibrio in hybrids of Argopecten scallops - Xiaoxu Qu; Xia Wang; Bo Liu; Min Chen; Junhao Ning; Haijun Liu; Guilong Liu; Xin Xu; Xiaotong Zhang; Kai Yu; He Xu; Xia Lu; et al. (Fish & Shellfish Immunology, 2023)

Characterization of TRAF genes and their responses to Vibrio anguillarum challenge in Argopecten scallops - Xia Wang; Xiaoxu Qu; Xia Lu; Min Chen; Junhao Ning; Haijun Liu; Guilong Liu; Xin Xu; Xiaotong Zhang; Kai Yu; He Xu; Bo Liu; et al. (Fish & Shellfish Immunology, 2023)

Cyclodextrin-functionalized magnetic alginate microspheres for synchronous removal of lead and bisphenol a from contaminated soil - Jianhua Qu; Zhuoran Li; Zhihuan Wu; Fuxuan Bi; Shuqi Wei; Min Dong; Qi Hu; Yifan Wang; Hui Yu; Ying Zhang (Chemical Engineering Journal, 2023)

Influence of Soil Plug on the Seismic Response of Bucket Foundations in Liquefiable Seabed - Xue-Qian Qu; Rui Wang; Jian-Min Zhang; Ben He (Journal of Marine Science and Engineering, 2023)
The suction installation process for bucket foundations for offshore wind turbines (OWTs) can cause the formation of soil plug within the bucket, which can affect the seismic performance of the OWT. Therefore, it is important to evaluate the influence of soil plug on the seismic performance of OWT on bucket foundations. In this study, a comprehensive set of high-fidelity solid–fluid coupled dynamic numerical simulations are conducted to analyze the seismic response of bucket foundations with a focus on the influence of soil plug and its potential mitigation. The influence of different bucket models, seabed soil densities, seabed inclination and reinforcement types, as well as soil plug removal techniques, are investigated. The results clearly show that the existence of soil plug has a significant unfavorable influence on the seismic performance of OWT on bucket foundations, especially for wide bucket foundations in mildly inclined seabeds, and should be considered in seismic design. Reinforcement methods, such as the application of an inner compartments, outer wings and inner pile, can improve the seismic performance of OWT on bucket foundations, with the application of an inner compartment being the most effective. Soil plug removal can alleviate the negative influence of soil plug, and should be adopted when possible.

Coated diammonium phosphate combined with Paecilomyces variotii extracts improves root architecture, enhances spring low temperature tolerance, and increases wheat yield - Qi Chen; Zhaoming Qu; Zixin Zhang; Guohua Ma; Mengyi Zhu; Jiadong Dan; Jun Wang; Shigang Zhang; Xinhua Ding; Min Zhang; Panfang Lu; Zhiguang Liu (Soil and Tillage Research, 2023)

High Fischer ratio peptide of hemp seed: Preparation and anti-fatigue evaluation in vivo and in vitro - Zhu Ying; Huang Yuyang; Li Meiying; Sun Bingyu; Liu Linlin; Lv Mingshou; Qu Min; Guan Huanan; Zhu Xiuqing (Food Research International, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Contrasting relationships between plant-soil microbial diversity are driven by geographic and experimental precipitation changes - Xiaoan Zuo; Shanshan Sun; Shaokun Wang; Ping Yue; Ya Hu; Shengnlong Zhao; Xinxin Guo; Xiangyun Li; Min Chen; Xujun Ma; Hao Qu; Weigang Hu; et al. (Science of The Total Environment, 2023)

Thermal reaction characteristics and microstructure evolution of aluminium nano-powder in various mixtures of oxygen and nitrogen atmosphere - Jiao Qu; Jun Deng; Zhen-Min Luo; Yang Xiao; Chi-Min Shu (Process Safety and Environmental Protection, 2023)

Numerical investigation on vortex control effect of pump-jet propulsion via porous blade tips - Yu Sun; Li-xin Qu; Geng Wang; Huang-hua Peng; Jia-min Guo (Ocean Engineering, 2023)

Development and validation of single-step microwave-assisted digestion method for determining heavy metals in aquatic products: Health risk assessment - Yong Min Lao; Cui Lan Qu; Bing Zhang; Hui Jin (Food Chemistry, 2023)

Air pollutant emissions and reduction potentials from municipal solid waste incineration in China - Ling Tang; Jing Guo; Ruxing Wan; Min Jia; Jiabao Qu; Ling Li; Xin Bo (Environmental Pollution, 2023)

Deposition effect of inhaled particles in the human: Accurate health risks of personal exposure to PAHs and their derivatives from residential solid fuel combustion - Rong Feng; Hongmei Xu; Yunxuan Gu; Min Gao; Yunlong Bai; Meixuan Liu; Zhenxing Shen; Jian Sun; Linli Qu; Steven Sai Hang Ho; Junji Cao (Atmospheric Environment, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Development and application of a multiplex qPCR assay for the detection of duck circovirus, duck Tembusu virus, Muscovy duck reovirus, and new duck reovirus - Yan Wen Yin; Chenyong Xiong; Kai Chuang Shi; Shou Yu Xie; Feng Long; Jun Li; Min Zheng; Xian Kai Wei; Shuping Feng; Sujie Qu; Wenjun Lu; Hongjin Zhou; et al. (Virus Genes, 2023)

Structure–performance correlation guided cerium-based metal–organic frameworks: Superior adsorbents for fluoride removal in water - Xiaofeng Tang; Wu Xia; Xiaolin Qu; Chaohai Wang; Wenjun Wang; Yuntao Liang; Yuxi Zeng; Weiping Xiong; Min Cheng; Biao Song; Chengyun Zhou; Xiaoying Zhao (Chemosphere, 2023)

Evaluation of bio-oil/biodiesel production from co-pyrolysis of corn straw and natural hair: A new insight towards energy recovery and waste biorefinery - Min Xiong; Jin Huang; Xinrui He; Zhihui Zhou; Xiangjiang Qu; Shah Faisal; Abdelfatah Abomohra (Fuel, 2023)

Estimation of sound speed profiles based on remote sensing parameters using a scalable end-to-end tree boosting model - Zhenyi Ou; Ke Qu; Min Shi; Yafen Wang; Jianbo Zhou (Frontiers in Marine Science, 2022)
Introduction In underwater acoustic applications, the three-dimensional sound speed distribution has a significant impact on signal propagation. However, the traditional sound speed profile (SSP) measurement method requires a lot of manpower and time, and it is difficult to popularize. Satellite remote sensing can collect information on a large ocean surface area, from which the underwater information can be derived. Method In this paper, we propose a method for reconstructing the SSP based on an extensible end-to-end tree boosting (XGBoost) model. Combined with satellite remote sensing data and Argo profile data, it extracts the characteristic matrix of the SSP and analyzes the contribution rate of each order matrix to reduce the introduction of noise. The model inverts the SSP above 1000 m in the South China Sea by using the root mean square error (RMSE) as the precision evaluation index. Result The results showed that the XGBoost model could better reconstruct the SSP above 1000 m, with a RMSE of 1.75 m/s. Compared with the single empirical orthogonal function regression (sEOF-r) model of the linear regression method, the RMSE of the XGBoost model was reduced by 0.59 m/s. Discussion For this model, the RMSE of the inversion results was smaller, the robustness was better, and the regression performance was superior to that of the sEOF-r model at different depths. This study provided an efficient tree boosting model for SSP reconstruction, which could reliably and instantaneously monitor the 3D sound speed distribution.

The expression and the tumor suppressor role of CLDN6 in colon cancer - Huinan Qu; Min Wang; Miaomiao Wang; Yuanyuan Liu; Chengshi Quan (Molecular and Cellular Biochemistry, 2022)

The different effects of intramuscularly-injected lactate on white and brown adipose tissue in vivo - Yaqian Qu; Siyu Chen; Lei Zhou; Min Chen; Lin Li; Yihan Ni; Jingquan Sun (Molecular Biology Reports, 2022)

First report of Colletotrichum queenslandicum causing leaf anthracnose on Dracaena cambodiana in China - Shumin Wang; Meijiao Hu; Xiangxiang Qu; Jinyu Yang; Zhaoyin Gao; Shuming Wang; Zhiqiang Liu; Min Li (Journal of General Plant Pathology, 2022)

Dolominol a and B, two new neolignans from Dolomiaea souliei (Franch.) C.Shih - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Jing-Xin Mao; Guowei Wang; Mingxing Liu; Zhi-Hua Liao; Min Chen (Natural Product Research, 2022)

Particle size shapes the prokaryotic microbial communities in mangrove sediments: A case study of Sanya, China - Wu Qu; Michael Vicent Shija; Jie Wu; Min Jin; Jianxin Wang; Runying Zeng; Zhuhua Chan (Acta Oceanologica Sinica, 2022)

Cerebral vasculitis caused by Talaromyces marneffei and Aspergillus niger in a HIV-positive patient: a case report and literature review - Yidong Gao; Man Qu; Chao Song; Lufeng Yin; Min Zhang (Journal of NeuroVirology, 2022)
Cerebral vasculitis is a long-standing but flourishing and fadeless research topic. Infections are a frequent cause of cerebral vasculitis, vital to diagnose due to involvement of specific anti-infection treatments. A 65-year-old man visited the hospital for his neurological symptoms without obvious inducements. After admission, radiological examination and comprehensive conventional microbiological tests (CMTs) revealed suspected intracranial infectious vasculitis. Metagenomic next-generation sequencing (mNGS) and reverse transcription-polymerase chain reaction further confirmed that his cerebral vasculitis was caused by Talaromyces marneffei ( T. marneffei ) and Aspergillus niger ( A. niger ) co-infection. The patient’s final diagnosis changed from initial herpetic encephalitis, due to the past history of cephalosome and facial herpes and non-significant antiviral therapeutic effects, to fungal cerebral vasculitis. The patient was discharged after use of targeted antifungal therapies on day 18 of his admission, and his associated symptoms disappeared completely at follow-up 3 weeks later. We first illustrated the presence of uncommon cerebral vasculitis caused by T. marneffei and A. niger in a human immunodeficiency virus-positive patient. In clinically suspected patients with infectious cerebral vasculitis, mNGS should be performed to detect potential pathogens if CMTs may not provide useful pathogenic clues, highlighting the importance of mNGS in the diagnosis and treatment of infectious diseases.

Hydroxysafflor yellow A can improve depressive behavior by inhibiting hippocampal inflammation and oxidative stress through regulating HPA axis - Zhiqiang Liu; Yongzhou Zou; Min He; Ping Yang; Xinhui Qu; Lijun Xu (Journal of Biosciences, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Himalaflavone A-E, five new flavonoids from Oxybaphus himalaicus - Xuanning Long; Fancheng Meng; Shenyue Qu; Hali Ji; Xiaozhong Lan; Min Chen (Natural Product Research, 2022)

Microporous modified atmosphere packaging to extend shelf life of fresh foods: A review - Ping Qu; Min Zhang; Kai Fan; Zhimei Guo (Critical Reviews in Food Science and Nutrition, 2022)

Responses of ecosystem respiration, methane uptake and nitrous oxide emission to drought in a temperate desert steppe - Ping Yue; Xiaoan Zuo; Kaihui Li; Xiangyun Li; Shaokun Wang; Xujun Ma; Hao Qu; Min Chen; Liangxu Liu; Tom Misselbrook; Qiang Yu (Plant and Soil, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Spatial and local environmental factors outweigh geo‐climatic gradients in structuring taxonomically and trait‐based β ‐diversity of benthic algae - Naicheng Wu; Shuchan Zhou; Min Zhang; Wenqi Peng; Kun Guo; Xiaodong Qu; Fengzhi He (Journal of Biogeography, 2021)
Aim Understanding the variation in biodiversity and its underlying drivers and mechanisms is a core task in biogeography and ecology. We examined (a) the relative contributions of species replacement (i.e., turnover) and richness difference (i.e., nestedness) to taxonomically and trait‐based β ‐diversity of stream benthic algae; (b) whether these two facets of β ‐diversity are correlated with each other; and (c) the relative contributions of local environmental, geo‐climatic and spatial factors to the two facets of β ‐diversity and their components. Location Hun‐Tai River Basin, northeastern China. Taxon Stream benthic algae. Methods A total of 157 sites were sampled. Mantel tests were used to examine the complementarities between the two facets of β ‐diversity and their components. Distance‐based redundancy analysis and variation partitioning were utilized to investigate the relative contributions of local environmental, geo‐climatic and spatial factors to each facet of β ‐diversity and their components. Results Weak correlations between taxonomically and trait‐based β ‐diversity and their components were detected, which indicated complementarity of ecological information. Taxonomically based total β ‐diversity was largely driven by turnover, whereas trait‐based total β ‐diversity was more driven by nestedness. Variation partitioning results indicated that local environmental and spatial factors contributed more than geo‐climatic variables to the total explained variation in taxonomically and trait‐based β ‐diversity. Main conclusions Different facets of β ‐diversity and their decomposition are important for understanding diversity patterns of benthic algae relative to abiotic factors. A high level of trait‐based convergence among benthic algae communities, despite high taxonomic divergence, demonstrated turnover of species with similar biological traits across our study region. Our study provides a trait‐based insight into stream benthic algae communities, which was less documented by previous freshwater studies that focused on regions undergoing recovery following human disturbances.

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Nitrogen fertilizer management affects remobilization of the immobilized cadmium in soil and its accumulation in crop tissues - Jun-Feng Wang; Wan-Li Li; Qu-Sheng Li; Li-Li Wang; Tao He; Fo-Peng Wang; Zhi-Min Xu (Environmental Science and Pollution Research, 2021)

The effects of flood pulse on multiple aquatic organisms in a seasonal shallow lake - Yang Liu; Min Zhang; Wenqi Peng; Naicheng Wu; Xiaodong Qu; Yang Yu; Yuhang Zhang; Chenyu Yang (Aquatic Ecology, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Optimizing Protein-Glutaminase Expression in Bacillus subtilis - Xiaoying Ouyang; Yingjie Liu; Ruidan Qu; Min Tian; Ting Yang; Rui Zhu; Hongliang Gao; Mingfei Jin; Jing Huang (Current Microbiology, 2021)

Surface Temperature Changes Projected by FGOALS Models under Low Warming Scenarios in CMIP5 and CMIP6 - Shang-Min Long; Kai-Ming Hu; Gen Li; Gang Huang; Xia Qu (Advances in Atmospheric Sciences, 2021)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

l-Glutamic acid induced the colonization of high-efficiency nitrogen-fixing strain Ac63 (Azotobacter chroococcum) in roots of Amaranthus tricolor - Yi-Fan Wang; Jun-Feng Wang; Zhi-Min Xu; Shao-Hua She; Jun-Qing Yang; Qu-Sheng Li (Plant and Soil, 2020)

Whole-Brain Monosynaptic Inputs to Hypoglossal Motor Neurons in Mice - Han Guo; Xiang-Shan Yuan; Ji-Chuan Zhou; Hui Chen; Shan-Qun Li; Wei-Min Qu; Zhi-Li Huang (Neuroscience Bulletin, 2020)
Hypoglossal motor neurons (HMNs) innervate tongue muscles and play key roles in a variety of physiological functions, including swallowing, mastication, suckling, vocalization, and respiration. Dysfunction of HMNs is associated with several diseases, such as obstructive sleep apnea (OSA) and sudden infant death syndrome. OSA is a serious breathing disorder associated with the activity of HMNs during different sleep–wake states. Identifying the neural mechanisms by which the state-dependent activities of HMNs are controlled may be helpful in providing a theoretical basis for effective therapy for OSA. However, the presynaptic partners governing the activity of HMNs remain to be elucidated. In the present study, we used a cell-type-specific retrograde tracing system based on a modified rabies virus along with a Cre/loxP gene-expression strategy to map the whole-brain monosynaptic inputs to HMNs in mice. We identified 53 nuclei targeting HMNs from six brain regions: the amygdala, hypothalamus, midbrain, pons, medulla, and cerebellum. We discovered that GABAergic neurons in the central amygdaloid nucleus, as well as calretinin neurons in the parasubthalamic nucleus, sent monosynaptic projections to HMNs. In addition, HMNs received direct inputs from several regions associated with respiration, such as the pre-Botzinger complex, parabrachial nucleus, nucleus of the solitary tract, and hypothalamus. Some regions engaged in sleep–wake regulation (the parafacial zone, parabrachial nucleus, ventral medulla, sublaterodorsal tegmental nucleus, dorsal raphe nucleus, periaqueductal gray, and hypothalamus) also provided primary inputs to HMNs. These results contribute to further elucidating the neural circuits underlying disorders caused by the dysfunction of HMNs.

Experimental investigation on the impact force of the dry granular flow against a flexible barrier - Xiao Siyou; Su Lijun; Jiang Yuanjun; Qu Xin; Xu Min; Hu Xiaobo; Liu Zhenyu (Landslides, 2020)

Assessment of potentially toxic pollutants and urban livability in a typical resource-based city, China - Min Tan; Hua Zhao; Gang Li; Junfeng Qu (Environmental Science and Pollution Research, 2020)

A new neolignan glycoside from Dolomiaea souliei - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Yun-Yi Tao; Zhi-Hua- Liao; Min Chen (Natural Product Research, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

Establishment of geochemical baseline and multiple assessment of vanadium pollution in sediment cores from the two cascade reservoirs, North China - Jiankang Wang; Wenqi Peng; Shaoming Wang; Bo Gao; Xiaodong Qu; Min Zhang; Dongyu Xu (Environmental Science and Pollution Research, 2020)

Unconformity-controlled dissolution contributes to reservoirs in the carbonate-rich Permian Fengcheng Formation, northwestern Junggar Basin, China - Kuanhong Yu; Yingchang Cao; Longwei Qiu; Peipei Sun; Yongqiang Yang; Changsheng Qu; Dewen Lei; Xiyu Jia; Min Wan; Zhijie Zhang (Carbonates and Evaporites, 2020)

Dopamine D1 and D2 receptors mediate analgesic and hypnotic effects of l-tetrahydropalmatine in a mouse neuropathic pain model - Yuan-Yuan Liu; Tian-Xiao Wang; Ji-Chuan Zhou; Wei-Min Qu; Zhi-Li Huang (Psychopharmacology, 2019)

Serratia microhaemolytica sp. nov., isolated from an artificial lake in Southern China - Juan Wang; Min-Ling Zheng; Jian-Yu Jiao; Wei-Jia Wang; Shuai Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Taxonomic structure and potential nitrogen metabolism of microbial assemblage in a large hypereutrophic steppe lake - Xiaodong Qu; Min Zhang; Yu Yang; Ying Xie; Ze Ren; Wenqi Peng; Xia Du (Environmental Science and Pollution Research, 2019)

Development of a novel bacterial surface display system using truncated OmpT as an anchoring motif - Chang-ye Hui; Yan Guo; Lisa Liu; Hao-qu Zheng; Hong-min Wu; Liu-zhuo Zhang; Wen Zhang (Biotechnology Letters, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

The anxiolytic effects of Bai Le Mian capsule, a traditional Chinese hypnotic in mice - Tian-Xiao Wang; Yu-Er Wu; Wei Xu; Wan-Kun Gong; Jian Ni; Wei-Min Qu; Zhi-Li Huang (Sleep and Biological Rhythms, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Pleistocene glaciation explains the disjunct distribution of the Chestnut‐vented Nuthatch (Aves, Sittidae) - Min Zhao; Yongbin Chang; Rebecca T. Kimball; Jian Zhao; Fumin Lei; Yanhua Qu (Zoologica Scripta, 2019)
Pleistocene climatic oscillations have played an important role in shaping many species’ current distributions. In recent years, there has been increasing interest in studying the effects of glacial periods on East Asian birds. Integrated approaches allow us to study past distribution range changes due to Pleistocene glaciation, and how these changes have affected current population genetic structure, especially for species with unusual distribution patterns. The Wuyi disjunction is the disjunct distribution of birds between the Wuyi Mountains in south‐eastern China and south‐western China. Although several species exhibit the Wuyi disjunction, the process behind this unusual distribution pattern has remained relatively unstudied. Therefore, we used the Chestnut‐vented Nuthatch Sitta nagaensis as a model species to investigate the possible causes of the Wuyi disjunction. Based on phylogenetic analyses with three mitochondrial and six nuclear regions, the Wuyi population of the Chestnut‐vented Nuthatch was closely related to populations in mid‐Sichuan, from which it diverged approximately 0.1 million years ago, despite the long geographical distance between them (over 1,300 km). In contrast, geographically close populations in mid‐ and southern Sichuan were genetically divergent from each other (more than half a million years). Ecological niche modelling suggested that the Chestnut‐vented Nuthatch has experienced dramatic range expansions from Last Interglacial period to Last Glacial Maximum, with some range retraction following the Last Glacial period. We propose that the Wuyi disjunction of the Chestnut‐vented Nuthatch was most likely due to recent range expansion from south‐western China during the glacial period, followed by postglacial range retraction.

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Lack of deuterium isotope effects in the antidepressant effects of (R)-ketamine in a chronic social defeat stress model - Kai Zhang; Hidetoh Toki; Yuko Fujita; Min Ma; Lijia Chang; Youge Qu; Shingo Harada; Tetsuhiro Nemoto; Akiko Mizuno-Yasuhira; Jun-ichi Yamaguchi; Shigeyuki Chaki; Kenji Hashimoto (Psychopharmacology, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Heterologous expression of Shigella dysenteriae serotype 1 O-antigen analog in Escherichia coli K-12 W3110 by transferring a minimum number of genes involved in O-polysaccharide biosynthesis - Yun Kong; Yajun Qu; Shengjun Wang; Peng George Wang; Min Chen (Biotechnology Letters, 2018)

Association between miR-146a rs2910164 polymorphism and specific cancer susceptibility: an updated meta-analysis - Xia Hao; Lingzi Xia; Ruoyi Qu; Xianglin Yang; Min Jiang; Baosen Zhou (Familial Cancer, 2018)

Effects of body mass index on the outcomes of in vitro fertilization in Chinese patients with polycystic ovary syndrome: a retrospective cohort study - Xiao-ming Pan; Zhong Lin; Nan Li; Jia-qi Wu; Dan-qing Chen; Yi-min Zhu; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Entire Frequency Domain Analysis of Rodent EEG and EMG Recordings Using Relative Thresholds - Ming-Ming Yan; Wei-Min Qu; Xin-Hong Xu; Zhi-Li Huang; Ming-Hui Yao (Sleep and Vigilance, 2017)

Gastrodin Attenuates Pentylenetetrazole-Induced Seizures by Modulating the Mitogen-Activated Protein Kinase-Associated Inflammatory Responses in Mice - Liming Chen; Xinan Liu; Hua Wang; Min Qu (Neuroscience Bulletin, 2017)

Five-year population dynamics of plateau pikas (Ochotona curzoniae) on the east of Tibetan Plateau - Jiapeng Qu; James C. Russell; Weihong Ji; Min Yang; Qianquan Chen; Wenjing Li; Yanming Zhang (European Journal of Wildlife Research, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Sediment heavy metals and benthic diversities in Hun-Tai River, northeast of China - Xiaodong Qu; Ze Ren; Min Zhang; Xiaobo Liu; Wenqi Peng (Environmental Science and Pollution Research, 2017)

Effects of sand burial on the survival and growth of two shrubs dominant in different habitats of northern China - Hao Qu; Ha-Lin Zhao; Xue-Yong Zhao; Xiao-An Zuo; Shao-Kun Wang; Min Chen (Environmental Monitoring and Assessment, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Erratum to: Phylogenetic position of the Wallcreeper Tichodroma muraria - Min Zhao; Per Alström; Urban Olsson; Yanhua Qu; Fumin Lei (Journal of Ornithology, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Development and characterization of twenty-nine novel polymorphic microsatellite loci in the mandarin fish Siniperca chuatsi - CHUN-MEI QU; XU-FANG LIANG; WEI HUANG; CHENG ZHAO; LIANG CAO; MIN YANG; CHANG-XU TIAN (Journal of Genetics, 2016)

Nematode‐trapping fungi and fungus‐associated bacteria interactions: the role of bacterial diketopiperazines and biofilms on Arthrobotrys oligospora surface in hyphal morphogenesis - Lei Li; Min Yang; Jun Luo; Qing Qu; Ying Chen; Lianming Liang; Keqin Zhang (Environmental Microbiology, 2016)
Summary In soil, nematode‐trapping fungi and bacteria often share microhabitats and interact with each other, but effects of fungus‐associated bacteria on its trap formation are underestimated. We have ascertained the presence of Stenotrophomonas and Rhizobium genera associated with A. oligospora GJ‐1. After A. oligospora GJ‐1 without associated bacteria (cured Arthrobotrys ) was co‐cultivated with Stenotrophomonas and its supernatant extract, microscopic study of hyphae from co‐cultivation indicated that bacterial biofilm formation on hyphae was related to trap formation in fungi and Stenotrophomonas supernatant extract. Four diketopiperazines (DKPs) were purified from Stenotrophomonas supernatant extract that could not induce traps in the cured Arthrobotrys . When cured Arthrobotrys was cultured with Stenotrophomonas and one of DKPs, polar attachment, bacterial biofilms on hyphae and trap formation in fungi were observed. After cured Arthrobotrys with bacterial biofilms was consecutively transferred several times on nutrient poor medium, trap formation disappeared with the disappearance of bacterial biofilms on hyphae. DKPs could facilitate chemotaxis of Stenotrophomonas towards fungal extract which was suggested to contribute to bacterial biofilms on hyphae. Furthermore, when cured Arthrobotrys was cultured with Stenotrophomonas and DKPs in soil, trap formation in fungi and bacterial biofilms on hyphae were also observed, and the fungal activity against nematode was enhanced.

Salidroside protects cortical neurons against glutamate-induced cytotoxicity by inhibiting autophagy - Wei-Yong Yin; Qiang Ye; Huan-Jie Huang; Nian-Ge Xia; Yan-Yan Chen; Yi Zhang; Qiu-Min Qu (Molecular and Cellular Biochemistry, 2016)

Phylogenetic position of the Wallcreeper Tichodroma muraria - Min Zhao; Per Alström; Urban Olsson; Yanhua Qu; Fumin Lei (Journal of Ornithology, 2016)

Targeting AMPK signalling pathway with natural medicines for atherosclerosis therapy: an integration of in silico screening and in vitro assay - Tiantong Ou; Xumin Hou; Shaofeng Guan; Jinjie Dai; Wenzheng Han; Ruogu Li; Wenxia Wang; Xinkai Qu; Min Zhang (Natural Product Research, 2016)

Characterizing the compositional variation of dissolved organic matter over hydrophobicity and polarity using fluorescence spectra combined with principal component analysis and two-dimensional correlation technique - Ben-Sheng Su; Zhen Qu; Xiao-Song He; Ying-Hao Song; Li-Min Jia (Environmental Science and Pollution Research, 2016)

Effects of habitat disturbance on the pollination system of Ammopiptanthus mongolicus (Maxim) Cheng f. at the landscape-level in an arid region of Northwest China - Min Chen; Xue-Yong Zhao; Xiao-An Zuo; Wei Mao; Hao Qu; Yang-Chun Zhu (Journal of Plant Research, 2016)

Use of flue gas desulfurization gypsum for leaching Cd and Pb in reclaimed tidal flat soil - Ping Yang; Xian Li; Ze-Jun Tong; Qu-Sheng Li; Bao-Yan He; Li-Li Wang; Shi-Hong Guo; Zhi-Min Xu (Environmental Science and Pollution Research, 2016)

Reactive oxygen species regulate programmed cell death progress of endosperm in winter wheat (Triticum aestivum L.) under waterlogging - Xiang-Xu Cheng; Min Yu; Nan Zhang; Zhu-Qing Zhou; Qiu-Tao Xu; Fang-Zhu Mei; Liang-Huan Qu (Protoplasma, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

Paeoniflorin exerts analgesic and hypnotic effects via adenosine A1 receptors in a mouse neuropathic pain model - Dou Yin; Yuan-Yuan Liu; Tian-Xiao Wang; Zhen-Zhen Hu; Wei-Min Qu; Jiang-Fan Chen; Neng-Neng Cheng; Zhi-Li Huang (Psychopharmacology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Preliminary Studies on Spanish Mackerel Fresh-Keeping Method in High-Voltage Electric Field - Ya-Xiang Bai; Yu-Cai Hu; Min Qu (Journal of Aquatic Food Product Technology, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Genome-wide analysis and expression of the calcium-dependent protein kinase gene family in cucumber - Xuewen Xu; Min Liu; Lu Lu; Min He; Wenqin Qu; Qiang Xu; Xiaohua Qi; Xuehao Chen (Molecular Genetics and Genomics, 2015)

Chemical constituents from Piper wallichii - Yan-Ni Shi; Lian Yang; Jin-Hua Zhao; Yi-Ming Shi; Yan Qu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Xing-Cong Li; Min Xu; Ying-Jun Zhang (Natural Product Research, 2015)

A new ellagic acid derivative from Polygonum runcinatum - Zhi-Hong Zhou; Min-Zhuo Liu; Meng-Hua Wang; Wei Qu; Jian-Bo Sun; Jing-Yu Liang; Fei-Hua Wu (Natural Product Research, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

Pin1 is Overexpressed and Correlates with Poor Prognosis in Gastric Cancer - Min Shi; Lingxiang Chen; Jun Ji; Qu Cai; Yingyan Yu; Bingya Liu; Zhenggang Zhu; Jun Zhang (Cell Biochemistry and Biophysics, 2015)

Polycephalomyces lianzhouensis sp. nov., a new species, co-occurs with Ophiocordyceps crinalis - Lei Wang; Hao-Hua Li; Yue-Qin Chen; Wei-Min Zhang; Liang-Hu Qu (Mycological Progress, 2014)

Piromelatine exerts antinociceptive effect via melatonin, opioid, and 5HT1A receptors and hypnotic effect via melatonin receptors in a mouse model of neuropathic pain - Yuan-Yuan Liu; Dou Yin; Li Chen; Wei-Min Qu; Chang-Rui Chen; Moshe Laudon; Neng-Neng Cheng; Yoshihiro Urade; Zhi-Li Huang (Psychopharmacology, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Heterochronic bilateral ectopic pregnancy after ovulation induction - Bo Zhu; Gu-feng Xu; Yi-feng Liu; Fan Qu; Wei-miao Yao; Yi-min Zhu; Hui-juan Gao; Dan Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of NO x and VOCs from five emission sources on summer surface O3 over the Beijing-Tianjin-Hebei region - Yu Qu; Junling An; Jian Li; Yong Chen; Ying Li; Xingang Liu; Min Hu (Advances in Atmospheric Sciences, 2014)

Two unrelated patients with rare Crigler-Najjar syndrome type I: two novel mutations and a patient with loss of heterozygosity of UGT1A1 gene - Yan Li; Yu-jin Qu; Xue-mei Zhong; Yan-yan Cao; Li-min Jin; Jin-li Bai; Xin Ma; Yu-wei Jin; Hong Wang; Yan-ling Zhang; Fang Song (Journal of Zhejiang University-SCIENCE B, 2014)

A new taxane diterpenoid from Taxus chinensis var. mairei - Zhi-Hong Zhou; Wei Qu; Min-Zhuo Liu; Jian-Bo Sun; Meng-Hua Wang; Jing-Yu Liang; Fei-Hua Wu (Natural Product Research, 2014)

Comparison of lisianthus (Eustoma grandiflorum) cultivars based on the selected regeneration media using anther culture - Xuhong Zhou; Xijun Mo; Suping Qu; Min Tian; Xuewei Wu; Min Wu; Jinze Li; Ying Luo; Jihua Wang; Min Gui (Horticulture, Environment, and Biotechnology, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Photosynthetic performance and growth traits in Pennisetum centrasiaticum exposed to drought and rewatering under different soil nutrient regimes - Yayong Luo; Xueyong Zhao; Hao Qu; Xiaoan Zuo; Shaokun Wang; Wenda Huang; Yongqing Luo; Min Chen (Acta Physiologiae Plantarum, 2014)

Is there a difference in cognitive development between preschool singletons and twins born after intracytoplasmic sperm injection or in vitro fertilization? - Lan-Feng Xing; Yu-Li Qian; Lu-Ting Chen; Fan-Hong Zhang; Xin-Fen Xu; Fan Qu; Yi-Min Zhu (Journal of Zhejiang University-SCIENCE B, 2014)

EDdb: A web resource for eating disorder and its application to identify an extended adipocytokine signaling pathway related to eating disorder - Min Zhao; XiaoMo Li; Hong Qu (Science China Life Sciences, 2013)

Initial results of precise orbit and clock determination for COMPASS navigation satellite system - Qile Zhao; Jing Guo; Min Li; Lizhong Qu; Zhigang Hu; Chuang Shi; Jingnan Liu (Journal of Geodesy, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Magnesium Deficiency Results in Damage of Nitrogen and Carbon Cross-talk of Maize and Improvement by Cerium Addition - Haiquan Zhao; Qiuping Zhou; Min Zhou; Chunxiao Li; Xiaolan Gong; Chao Liu; Chunxiang Qu; Ling Wang; Wenhui Si; Fashui Hong (Biological Trace Element Research, 2012)

Cryotherapy is Associated with Improved Clinical Outcomes of Sorafenib Therapy for Advanced Hepatocellular Carcinoma - Yongping Yang; Yinying Lu; Chunping Wang; Wenlin Bai; Jianhui Qu; Yan Chen; Xiujuan Chang; Linjing An; Lin Zhou; Zhen Zeng; Min Lou; Jiyun Lv (Cell Biochemistry and Biophysics, 2012)

Physical and Sensory Properties of Electrohydrodynamic (EHD) Dried Scallop Muscle - Ya-Xiang Bai; Gui-Juan Yang; Yu-Cai Hu; Min Qu (Journal of Aquatic Food Product Technology, 2012)

Expression and Clinical Significance of CK19 and CK20 Expressions in Transverse Mesocolon Biopsies from Patients with Gastric Carcinoma - Guo-Rui Sun; Xiao-Yuan Dong; Qing-Si He; Hui Qu; Yan-Min Wang (Cell Biochemistry and Biophysics, 2012)

Origin and geological significance of the 1.81 Ga hyalophane-rich pegmatite veins from the high-pressure granulite terrain in the Central Zone of North China Craton - Min Qu; JingHui Guo; Yong Lai; Peng Peng; Fu Liu (Science China Earth Sciences, 2012)

Reproduction of plateau pika (Ochotona curzoniae) on the Qinghai–Tibetan plateau - Jiapeng Qu; Ming Liu; Min Yang; Yanming Zhang; Weihong Ji (European Journal of Wildlife Research, 2012)

Determination of Trophic Transfer at a Created Intertidal Oyster (Crassostrea ariakensis) Reef in the Yangtze River Estuary Using Stable Isotope Analyses - Wei-min Quan; Austin T. Humphries; Li-yan Shi; Ya-qu Chen (Estuaries and Coasts, 2012)

Isolation, characterization and docking studies of 2,3-dihydroxybiphenyl 1,2-dioxygenase from an activated sludge metagenome - Min Gou; Yuanyuan Qu; Bingwen Xu; Jiti Zhou; Xinliang Li; Hao Zhou (Biotechnology Letters, 2012)

Excess Thyroid Hormone Inhibits Embryonic Neural Stem/Progenitor Cells Proliferation and Maintenance through STAT3 Signalling Pathway - Chunhai Chen; Zhou Zhou; Min Zhong; Maoquan Li; Xuesen Yang; Yanwen Zhang; Yuan Wang; Aimin Wei; Mingyue Qu; Lei Zhang; Shangcheng Xu; Shude Chen; et al. (Neurotoxicity Research, 2011)

Bioremediation efficiencies of Gracilaria verrucosa cultivated in an enclosed sea area of Hangzhou Bay, China - Yuan Zi Huo; Shan Nan Xu; Yang Yang Wang; Jian Heng Zhang; Yin Jiang Zhang; Wei Ning Wu; Ya Qu Chen; Pei Min He (Journal of Applied Phycology, 2011)

Population genetic structure and phylogeographical pattern of rice grasshopper, Oxya hyla intricata, across Southeast Asia - Tao Li; Min Zhang; Yanhua Qu; Zhumei Ren; Jianzhen Zhang; Yaping Guo; K. L. Heong; Bong Villareal; Yang Zhong; Enbo Ma (Genetica, 2011)

TSdb: A database of transporter substrates linking metabolic pathways and transporter systems on a genome scale via their shared substrates - Min Zhao; YanMing Chen; DaCheng Qu; Hong Qu (Science China Life Sciences, 2011)

Up-regulation of growth factor independence 1 in endotoxin tolerant macrophages with low secretion of TNF-α and IL-6 - Min-Fang Zhu; Jing Zhang; Jie-Ming Qu; Hui-Jun Zhang; Shuang-Cheng Zhou; Sheng-Fu Dong; Hong-Ni Jiang; Hanssa Summah (Inflammation Research, 2010)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

A phylogenetic analysis of laughingthrushes (Timaliidae: Garrulax ) and allies based on mitochondrial and nuclear DNA sequences - Xu Luo; Yan Hua Qu; Lian Xian Han; Shou Hsien Li; Fu Min Lei (Zoologica Scripta, 2009)
The interspecific relationships among extant laughingthrushes have been unclear for a long time and this has resulted in a confusing taxonomic history. Recent advances in molecular methods have greatly improved the resolution of the phylogeny of birds; however, little works has been done on this specific group because of the inaccessibility to many species. This diverse group includes 50 species mostly distributed in South China and South‐east Asia, and were traditionally arranged into the genus Garrulax , for which the non monophyly had been questioned by previous molecular studies. In this study, we infer a phylogeny for 23 Garrulax species and 20 species from close related genera. Mitochondrial data or combined with nuclear sequences both indicate paraphyly of Garrulax , dividing Garrulax species into two groups. Based on these results, we suggest resurrecting the genus name Trochalopteron Blyth, 1843 for one group and retaining Garrulax for the other pending further study. Using dating methods with a secondary calibration point, we develop a profile of the speciation history of laughingthrushes, which suggests that the Hengduan Mountains might not be the centre of origin for these birds as previously suggested.

The hepatitis B virus protein MHBs(t) sensitizes hepatoma cells to TRAIL-induced apoptosis through ERK2 - Xiaohong Liang; Juan Du; Yugang Liu; Min Cui; Chunhong Ma; Lihui Han; Zhonghua Qu; Zhiyong Zhang; Zhaohui Sun; Lining Zhang; Youhai H. Chen; Wensheng Sun (Apoptosis, 2007)

The GUS reporter-aided analysis of the promoter activities of a rice metallothionein gene reveals different regulatory regions responsible for tissue-specific and inducible expression in transgenic Arabidopsis - Shiyou Lü; Hongya Gu; Xiaojing Yuan; Xiaoming Wang; Ai-Min Wu; Lijia Qu; Jin-Yuan Liu (Transgenic Research, 2007)

Postglacial colonization of the Tibetan plateau inferred from the matrilineal genetic structure of the endemic red‐necked snow finch, Pyrgilauda ruficollis - YAN HUA QU; PER G. P. ERICSON; FU MIN LEI; SHOU HSIEN LI (Molecular Ecology, 2005)
Most phylogeographical studies of postglacial colonization focus on high latitude locations in the Northern Hemisphere. Here, we studied the phylogeographical structure of the red‐necked snow finch Pyrgilauda ruficollis , an endemic species of the Tibetan plateau. We analysed 879 base pairs (bp) of the mitochondrial cytochrome b gene and 529 bp of the control region in 41 birds from four regional groups separated by mountain ranges. We detected 34 haplotypes, 31 of which occurred in a single individual and only three of which were shared among sampling sites within regional groups or among regional groups. Haplotype diversity was high ( h = 0.94); nucleotide diversity was low (ð = 0.00415) and genetic differentiation was virtually non‐existent. Analyses of mismatch distributions and geographically nested clades yielded results consistent with contiguous range expansion, and the expansion times were estimated as 0.07–0.19 million years ago (Ma). Our results suggest that P. ruficollis colonized the Tibetan plateau after the extensive glacial period (0.5–0.175 Ma), expanding from the eastern margin towards the inner plateau. Thus, in contrast to many of the postglacial phylogeographical structures known at high latitudes, this colonization occurred without matrilineal population structuring. This might be due to the short glacial cycles typical of the Tibetan plateau, adaptation of P. ruficollis to cold conditions, or refugia and colonized habitat being semicontinuous and thus promoting population mixing.

Molecular mechanism of prostaglandin D2-mediated non-REM sleep homeostasis studied by gene-knockout mice - Naomi EGUCHI; Wei-Min QU; Zhi-Li HUANG; Mie SAKATA; Shuh NARUMIYA; Jiang-Fan CHEN; Yoshihiro URADE; Osamu HAYAISHI (Sleep and Biological Rhythms, 2004)

Lack of rebound of non-rapid eye movement sleep after sleep deprivation in adenosine A2A receptor knockout mice - Mie SAKATA; Naomi EGUCHI; Wei-Min QU; Zhi-Li HUANG; Jiang-Fan CHEN; Michael A. SCHWARZSCHILD; Yoshihiro URADE; Osamu HAYAISHI (Sleep and Biological Rhythms, 2004)

Adenosine A2A receptor deficiency attenuates the somnogenic effect of prostaglandin D2 - Wei-Min QU; Zhi-Li HUANG; Takatoshi MOCHIZUKI; Naomi EGUCHI; Jiang-Fan CHEN; Michael A. SCHWARZSCHILD; Stephen J. FINK; Yoshihiro URADE; Osamu HAYAISHI (Sleep and Biological Rhythms, 2004)

Priorities for the conservation of avian biodiversity in China based on the distribution patterns of endemic bird genera - Fu-Min Lei; Yan-Hua Qu; Qian-Qian Tang; Shu-Cheng An (Biodiversity and Conservation, 2003)

Detection and analysis of QTLs for ferrous iron toxicity tolerance in rice, Oryza sativa L. - Jian-lin Wan; Hu-qu Zhai; Jian-min Wan; H. Ikehashi (Euphytica, 2003)

Conservation on diversity and distribution patterns of endemic birds in China - Fu-Min Lei; Yan-Hua Qu; Jian-Li Lu; Yao Liu; Zuo-Hua Yin (Biodiversity and Conservation, 2003)